On a class of exact locally conformal cosymlectic manifolds - I. Mihai; L. Verstraelen; R. Rosca (International Journal of Mathematics and Mathematical Sciences)
An almost cosymplectic manifold M is a (2m+1)-dimensional oriented Riemannian manifold endowed with a 2-form Ω of rank 2m, a 1-form η such that Ωm Λ η≠0 and a vector field ξ satisfying iξΩ=0 and η(ξ)=1. Particular cases were considered in [3] and [6].